(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
This article is about the relation and harmonization between maternity, breastfeeding and work outside the home, in order to determine whether the rights granted, mean while an assignment of rights and recognition to women. Demand the right of women to decide about their own body, without being subject to other decisions and strive for the expansion of citizenship; at the same time offers aware and active resistance to generate the necessary mechanisms to meet those objectives. Therefore, the discrepancies that emerge in everyday life are evident: laws that give life to the rights for the protection of women and the reality that drives them singly to walk along paths where the interstices carried them to circumvent the permanent tensions where their personal, family, work, projects among others. they are minimised, relegated, postponed or cancelled; When should legally be guaranteed.